2019
DOI: 10.6026/97320630015194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rotavirus and hepatitis A virus by worldwide climatic changes during the period between 2000 and 2013

Abstract: Enteric viruses are present in the environment as a result of the discharge of poorly or untreated wastewater. The spread of enteric viruses in the environment depend to human activities like stools of infected individuals ejected in the external environment can be transmitted by water sources and back to susceptible individuals for other cycles of illness. Among the enteric viruses Rotaviruses (RV) and Hepatitis A viruses (HAV) is the most detected in wastewater causing gastroenteritis and acute hepatitis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Climate conditions, especially ambient temperature, precipitation and humidity, were connected with the survival, reproduction, distribution and abundance of the intermediate vectors, and the physiological conditions, immune responses and crowding occurrence of the specific hosts ( Monto, 2004 ; Campbell et al., 2015 ; Paz, 2015 ), thus increasing the outbreak risk of the epidemic of respiratory infectious diseases. Worldwide climate changes, mainly temperature and carbon dioxide (CO 2 ) variations, had the possibility to affect the mutation of rotavirus and hepatitis A virus ( Tarek et al., 2019 ). To date, the evidence on climatic influences on the evolution of respiratory CoVs has been still lacking.…”
Section: Environmental Impactsmentioning
confidence: 99%
“…Climate conditions, especially ambient temperature, precipitation and humidity, were connected with the survival, reproduction, distribution and abundance of the intermediate vectors, and the physiological conditions, immune responses and crowding occurrence of the specific hosts ( Monto, 2004 ; Campbell et al., 2015 ; Paz, 2015 ), thus increasing the outbreak risk of the epidemic of respiratory infectious diseases. Worldwide climate changes, mainly temperature and carbon dioxide (CO 2 ) variations, had the possibility to affect the mutation of rotavirus and hepatitis A virus ( Tarek et al., 2019 ). To date, the evidence on climatic influences on the evolution of respiratory CoVs has been still lacking.…”
Section: Environmental Impactsmentioning
confidence: 99%
“…In addition, the effect of meteorological factors on viral transmission and outbreak at the host population have not yet been determined. It was reported that extreme meteorological factors can accelerate the mutation of viruses [ 9 , 10 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In this study, in order to find out the key climatic features of two coronavirus outbreaks in Wuhan and Guangdong in 2019 and 2002, respectively, we analyzed the climate data (mean temperature, maximum temperature, minimum temperature, precipitation, hours of sunshine, relative humidity) of Wuhan and Guangdong from 1951 to 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Shellfish are known to accumulate human pathogens, such as human enteric viruses (e.g., rotavirus in mussels [ 52 , 53 ], enterovirus [ 32 , 54 ], HAV [ 26 , 55 ], and norovirus [ 27 , 56 , 57 ] in oysters).…”
Section: Discussionmentioning
confidence: 99%